Effect of ph and ionic strength on permeate flux during separation of lactobacillus plantarum by using hollow fiber crossflow microfiltration - Abdullah, Nor Anira (2010)
Microfiltration is a separation process used for cell harvesting in downstream process. Current research focused on the factor affecting the process of cell separation from fermentation broth to be recycled into the fermenter. The efficiency of solute separation by microfiltration can be influenced by solution pH and ionic strength. The objectives of this research is to study the effects of pH solution which is pH 4.5, 5.5, 6.5, 7.5, 8.5 and ionic strength on permeate flux of separation of Lactobacillus plantarum bacteria. For this research, the 0.2, 0.4, 0.6, 0.8 and 1.0 M of salt concentration are also used. At pH 8.5, permeate flux is the highest due to the electrostatic repulsion between the Lactobacillus plantarum bacteria and the surface of the membrane. The lowest permeate flux is at 1.0 M of ionic strength due to compaction of membrane and results in reduction of effective permeability. As conclusion, flux can be affected by pH solution and addition of salt. Increase in pH solution resulted in increase in permeate flux and addition of salt decreases permeate flux.